2022
DOI: 10.1007/s40279-022-01664-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Sports Schools on Holistic Athlete Development: A Mixed Methods Systematic Review

Abstract: Background To understand the multiple and wide-ranging impacts of intensified youth sport, the need for a holistic approach to athlete development has recently been advocated. Sports schools are an increasingly popular operationalisation of intensified youth sport, aiming to offer an optimal environment for holistic development by combining sport and education. Yet, no study has systematically explored the impacts associated with sports schools. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 136 publications
6
37
0
1
Order By: Relevance
“…Jonker et al (2009) assessed the performance based on career choices whereas the present study used scholastic tests and grade points. The findings of the present study are, however, in line with the findings by Thompson et al (2022) who found that attending a sport school does not have a positive effect on academic success. Two reasons can be identified for the previously mentioned difference in the development of ESS students vs. non-studentathletes in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Jonker et al (2009) assessed the performance based on career choices whereas the present study used scholastic tests and grade points. The findings of the present study are, however, in line with the findings by Thompson et al (2022) who found that attending a sport school does not have a positive effect on academic success. Two reasons can be identified for the previously mentioned difference in the development of ESS students vs. non-studentathletes in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, athletic demands interfered less with academic tasks (Storm and Eske, 2022). Additionally, the support service in the present study allowed student-athletes with AA to receive more similar results to their peers at comprehensive schools which has previously been defined as problematic (Thompson et al, 2022). However, the support service AA seems to be selective as it only allows athletes in individual sports to participate.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations